Two patients with Hermansky Pudlak syndrome type 2 and novel mutations in AP3B1 - Matt Wenham; Samantha Grieve; Michelle Cummins; Matthew L. Jones; Sarah Booth; Rachel Kilner; Philip J. Ancliff; Gillian M. Griffiths; Andrew D. Mumford (Haematologica, 2010)
Hermansky Pudlak syndrome type 2 (HPS2) is a rare disorder associated with mutations in the Adaptor Protein 3 (AP-3) complex, which is involved in sorting transmembrane proteins to lysosomes and related organelles. We now report 2 unrelated subjects with HPS2 who show a characteristic clinical phenotype of oculocutaneous albinism, platelet and T-lymphocyte dysfunction and neutropenia. The subjects were homozygous for different deletions within AP3B1 (g.del180242-180866, c.del153-156), which encodes the AP-3β3A subunit, resulting in frame shifts and introduction of nonsense substitutions (p.E693fsX13, p.E52fsX11). In the subject with p.E693fsX13, this resulted in expression of a truncated variant β3A protein. Cytotoxic T-lymphocyte (CTL) clones from both study subjects showed increased cell-surface expression of CD63 and reduced cytotoxicity. Platelets showed impaired aggregation and reduced uptake of 3H-serotonin. These findings are consistent with CTL granule and platelet dense granule defects, respectively. This report extends the clinical and laboratory description of HPS2.